Evaluation of MR safety for a new liquid embolic device. (18th October 2013) - Audet-Griffin, Annabelle J; Pakbaz, Sean; Shellock, Frank G
Abstract : Background: As an alternative to conventional treatments, a new liquid embolic device (Neucrylate) may be used to treat aneurysms or arteriovenous malformation (AVMs). Because this device contains metal for opacification, an investigation was performed to evaluate MRI issues for this liquid embolic device. Methods: The liquid embolic device was evaluated for magnetic field interactions (translational attraction and torque) at 3 T, MRI-related heating at 1.5 T/64 MHz and 3 T/128 MHz and artifacts at 3 T using standardized techniques. In each case, MRI-related heating was assessed with the liquid embolic device in a gelled saline-filled phantom and MRI was performed using relatively high levels of radiofrequency energy. Artifacts were characterized using T1-weighted spin echo and gradient echo pulse sequences. Additionally, conductivity (ie, electrical resistance) measurements were recorded. Results: The liquid embolic device exhibited no magnetic field interactions. Heating was at the same level as background temperature rises (ie, the temperatures recorded without the liquid embolic device present in the phantom) under 1.5 T/64 MHz (highest temperature change 1.4°C) and 3 T/128 MHz (highest temperature change 1.8°C) MRI conditions. Artifacts were small in relation to the size and shape of the liquid embolic device. The device was found to pose no risks with regard to the conductivity of the material. Conclusions: These findings demonstrate that it is acceptable for a patient with this new liquid embolic device to undergo MRI at ≤3 T. Notably, the associated artifacts are unlikely to create issues for diagnostic MRI examinations.